The Effect of Using Problem Based Learning Model (PBL) on Mathematics Learning Outcomes of Class VIII Students at SMP Negeri 2 Tapian Dolok - Damanik, Delimaya; Sidabutar, Ropinus (EduMatika: Jurnal MIPA, 2023)
The aim of this research is to determine the effect of using the Problem Based Learning (PBL) learning model on the mathematics learning outcomes of class VIII students at SMP Negeri 2 Tapian Dolok. The type of research used in this research is quantitative research in the form of quasi-experimental research with a Nonequivalent Control Group Design. The population in this study was all students in class VIII of SMP Negeri 2 Tapian Dolok T.A 2023/2024, and the sample in this study was class VIII-1 as the experimental class and class VIII-2 as the control class. The instruments used in this research are validity, reliability, level of difficulty of test items and distinguishing power of test items. The research results showed that the average score of students who used the Problem Based Learning (PBL) learning model was 72.03, while the average score of students without using the Problem Based Learning (PBL) learning model was 62.7. The mathematics learning outcomes of students who use the Problem Based Learning (PBL) learning model are higher than those without the Problem Based Learning (PBL) learning model (t_count 2.1 > t_table 1.67 with a significance level of 0.05). This it can be concluded that there is an influence of the use of the Problem Based Learning (PBL) learning model on the mathematics learning outcomes of class VIII students at SMP Negeri 2 Tapian Dolok